O impacto de tecnologias sociais na mudança comportamental em alunos de rede pública de Santa Luzia do Itanhy – Se - Moreira, Alexandre Pedro (2022)
Social Technologies (TS) are the result of the advancement of the process of solving society's everyday problems. They are based on popular knowledge, creativity and the availability of resources in the locality from which they emerge. The TS have explicit objectives of improving the quality of life, social inclusion and empowerment of the less favored parts of the population. This research discusses the effects of STs on the human behavior of those who interact with them. In its cut, the work seeks to capture and identify the impact of TS developed by IPTI on the behavior of students in the municipality of Santa Luzia do Itanhy, state of Sergipe. Methodologically, it is a bibliographic, qualitative and exploratory approach. The research makes use of the SENNA, ENRI, LIKERT Scale, Scarpi's Aggregative and Wilder's Stochastic instruments for empirical investigation of the study. Models the observed population in two groups, treated and control. The instruments showed that IPTI students, treated group, do not have more enhanced socio-emotional and empathic characteristics than students who did not participate in the projects, control group. From the treated group, samples composed of veteran students from each of those TS were selected, structuring the focus groups. The results, from the point of view of the focus groups, showed that the STs under examination were important tools for social transformation, contributing positively to the interpersonal behavior of the participants in terms of empathy and socio-emotional skills. However, the results, according to the measurement instruments, verified between the treated and control groups, did not prove significant empirical evidence. The conclusion obtained at the end of the investigation is that the TS of IPTI are relevant in the process of personal development of their students, but they need to advance in methodologies for their interpersonal evolution. The Institute must establish a satisfactory monitoring method that can measure the real impacts of its SW on students and the community that is inserted, before, during and after the projects.